Efektivitas Penerapan Aplikasi Sicantik di Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu, Perindustrian dan Tenaga Kerja Kota Bukittinggi - Eliya Putri Utami; Aldri Frinaldi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This study aimed to determine the effectiveness of implementing the SICANTIK application in the One Stop Services Investment Office, Industry and Labor in the City of Bukittinggi. The SICANTIK application is an application that aims to provide services regarding licensing that are directly related to the community, and this is one of the government's efforts to provide quality public services to the community. This research is descriptive using qualitative methods. Informants were selected using purposive sampling technique. In data collection, research instruments were used in the form of field observations and interviews with several informants, then documentation study was used for documents in the study. The technique of testing the validity of the data used the triangulation method. While the data analysis technique is done by reducing data, displaying data and drawing conclusions from the research that has been carried out. The results of this study indicate that knowing the effectiveness of implementing the SICANTIK application in the One Stop Services Investment Office, Industry and Labor of the City of Bukittinggi is not effective enough.